Peningkatan Literasi Digital Siswa SMK dalam Menghadapi Bahaya Judi Online - Sinaga, Mikha; Simanjuntak, Peter; Tambunan, Mutiha; Hia, Charistian (Publikasi Pengabdian Masyarakat, 2025)
The increasing use of digital technology among vocational school students has had a positive impact in terms of access to information and skills development. However, this phenomenon has also opened up a gap for the emergence of online gambling threats, which are increasingly widespread among teenagers. Online gambling often targets young age groups through games and applications that seem harmless, which can lead to addiction and financial loss. On the other hand, the level of digital literacy among vocational school students is still relatively low. Although they are skilled in using digital devices, many do not understand the risks involved, such as the dangers of online gambling. This lack of understanding is exacerbated by limited education on digital ethics and wise internet use in schools, as well as a lack of awareness among parents and teachers regarding these potential risks. The importance of digital literacy is a solution to this problem, because with a good understanding, students can recognize and avoid the dangers of online gambling. However, educational programs on digital literacy and online gambling prevention are still limited, and many schools lack the resources to provide adequate training. As a solution, an empowerment program is needed for vocational school students through digital literacy training that aims to increase their awareness of the risks of online gambling, as well as teach them the responsible use of technology. This program also requires support from schools, parents, and the community to create a safe and healthy digital environment for students. The target output of this activity is scientific papers published in national journals with ISSN. The activities that will be carried out start from giving pretests to students to see students' knowledge of online gambling. After that, counseling is carried out on the negative impacts of online gambling. Then a posttest is carried out to see students' understanding of the material that has been presented.